Use of Glass Ionomer Sealants in The Prevention of Occlusal Caries in Pediatric Permanent Teeth - Eluama, Merniwati Sherly; Pinat, Leny Marlina A.; Pay, Mery Novaria; Obi, Applonia Leu; Wali, Agusthinus (Dental Therapist Journal, 2024)
In Indonesia, according to the Riskesdas data, only 0.1% of 15-year-old children received fissure sealant treatment. Glass ionomer sealants can prevent caries on newly erupted permanent molars and are a good alternative because they are cheaper, painless, and easy to apply. The study aimed to evaluate the retention of glass ionomer sealants in preventing occlusal caries on permanent molars in children. The research method used an experimental design. The independent variable was the filling of deep fissures with Fuji VII glass ionomer, and the dependent variable was the occlusal status of the left and right lower first permanent molars, which included teeth that had been sealed with glass ionomer (intact sealant, partially lost, completely lost, either caries-free or carious). The population consisted of primary school children in Manefu, East Baumata Village. The research sample was selected using purposive sampling, targeting primary school children aged 7-10 years at SD Manefu who had deep fissures and were willing to participate. Data collection involved clinical trials, including sealing the left and right lower first permanent molars with Fuji VII glass ionomer and evaluating the sealant retention after six months. Data were processed and analyzed using descriptive statistical tests. The results showed that nine molars had good retention (23.68%), five molars had partially lost their sealant (13.15%), 31.57% of molars were caries-free despite losing their entire sealant, and 31.57% of molars developed caries after losing their entire sealant. Overall, 26 molars (68.42%) treated with fissure sealing were protected from caries. Initial enamel caries lesions occurred in 31.58% of sealed molars whose sealants had dislodged. In conclusion, the use of glass ionomer sealants demonstrated a retention effect and prevented occlusal caries on permanent molars in children by up to 68.42%.